Development and application of polymeric materials for heavy metal ions recovery from industrial and mining wastewaters - Saad, Dalia (My University, 2012)
Contamination of water bodies by heavy metals and metalloids is an established problem and several studies have been conducted to deal with it. South Africa is amongst those countries whose water systems are most affected as a result of intensive mining activities. This research was dedicated to the development of insoluble chelating polymers for use as adsorbents to abstract heavy metal ions from mining and industrial wastewater. Branched polyethylenimine (PEI), well known for its metal chelating potential, was cross linked by epichlorohydrin in order to convert it into a water-insoluble form. The water-insoluble property gives the advantage of being used in situ and a possibility of regeneration and re-use, making it a more feasible and cost-effective method. Its surface was also modified for selective removal of specifically-targeted heavy metal and metalloid ions. The binding affinity of the synthesized materials to heavy metal and metalloid ions has been determined as well as their ability to be regenerated for reuse. These processes demonstrated that cross-linked polyethylenimine (CPEI) exhibited good complexation ability with high affinity to Cr and some divalent metal ions such as Fe, Zn, and Ni. On the other hand, it showed very poor ability to bind oxo-anions such as SeO32- and AsO2- which has been attributed to the unavailability of suitable functional groups to interact with these ions. The observed order of complexation was: Cr > Zn> Fe >> Ni > Mn > Pb >> As > U > Se. The phosphonated polyethylenimine (PCPEI) showed high selectivity for As, Mn and uranyl ions. The observed order of removal was: U > Mn> Ni > Zn > As >> Cr > Pb > Fe >> Hg > Se; whereas the suffocated polyethylenimine (SCPEI) exhibited high affinity to Se, and Hg. The observed order of adsorption was: Hg > Se >> U > Zn >Pb > Ni >> As > Cr > Fe. v The adsorption behaviour of these polymeric materials involved more than one mechanism such as complexation, normal surface charge exchange, and anion replacement and all these mechanisms are governed by the functional groups. The nitrogen atom on the chelating group (-NH) in the cross-linked polyethylenimine; the phosphorus atom on the chelating group (-PO3H2) in phosphonated cross-linked polyethylenimine; and sulphur atom on the chelating group (-SO3H) in suffocated cross-linked polyethylenimine act as Lewis bases and donate electrons to metal cations which are considered Lewis acids. The existence of the chelating groups in SCPEI and PCPEI facilitate the removal of oxo-anions through anion replacement since they exist as bases in solution and hence cannot be electron acceptors. Thus, the expected mechanism is the normal anion replacement. This mechanism can explain the high removal of Se by SCPEI since Se has similar chemical behaviour as sulphur and are in the same group in the periodic table. As such they can easily replace each other. Sulphur is released from the polymer into the solution by replacing the selenium ions in the polymer. Similar behaviour occurs between phosphorus in PCPEI and arsenic ions as As and P belong to the same group in the periodic table and hence have similarities in their chemical behaviour. The Langmuir and Freundlich isotherm models were used to interpret the adsorption nature of the metal ions onto synthesized polymers. The Freundlich isotherm was found to best fit and describe the experimental data describing the adsorption process of metal and metalloid ions onto the synthesized polymeric materials The kinetic rates were modelled using the pseudo first-order equation and pseudo second-order equation. The pseudo second-order equation was found to explain the adsorption kinetics most effectively implying chemisorption. vi The thermodynamic study of the adsorption of metals and metalloids by the synthesized CPEI, PCPEI and SCPEI resulted in high activation energies > 41 KJ mol-1 which confirm chemisorption as a mechanism of interaction between adsorbate and adsorbent. So far, the developed polymeric materials showed good results and have potential to be applied successfully for remediation of heavy metal-polluted waters, and they have potential for use in filter systems for household use in communities that use borehole water impacted by mining and industrial waste waters. The desorbed metals can be of use to metal processing industries.
M.Sc., Faculty of Science, University of the Witwatersrand, 2011
Keywords: Polymers; Transition metal complexes; Heavy metals (absorption and adsorption); Sewage (purification, biological treatment)